State and Human Rights: Challenges, Responsibility, and Compliance in the International Sphere - López Ruiz, Iliana; Pineda Champutiz, Diana (Universidad Hemisferios, 2026)
This study analyzes State responsibility for human rights violations within the framework of international law. The central objective is to examine the legal foundations of this responsibility, the normative sources that support it, and the mechanisms for supervision and enforceability at the international and regional levels. Through a theoretical and doctrinal analysis, the study reviews the constitutive elements of the State and its essential functions in guaranteeing human rights, addressing the evolution of these rights and their relationship with international obligations. The methodology used is qualitative, based on a documentary review of international norms, jurisprudence, and specialized doctrine. Normative and critical analysis methods are employed to evaluate the relationship between State sovereignty and international commitments regarding human rights. Among the main findings, the study highlights that international law imposes on States the obligation to respect, protect, and guarantee human rights, which extends beyond their internal jurisdiction and entails supranational oversight mechanisms. The role of human rights protection systems, such as the UN and the Inter-American Court of Human Rights, is examined, identifying challenges in the effective implementation of their decisions. From this perspective, the article offers a critical reflection on the structural limitations of the international human rights protection system and highlights the need to strengthen domestic mechanisms for the implementation of international decisions.